2018
DOI: 10.3390/molecules23081987
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Origanum vulgare Suppresses Propionibacterium acnes-Induced Inflammatory Responses in Human Monocyte and Mouse Ear Edema Models

Abstract: Acne vulgaris (acne) is a common inflammatory skin disorder, and Propionibacterium acnes plays a major role in the development and progression of acne inflammation. Herbs possessing antimicrobial and anti-inflammatory activity have been applied as a medical option for centuries. In this study, we examined the suppressive effect of ethanolic oregano (Origanum vulgare) extract on live P. acnes-induced in vivo and in vitro inflammation. Following ethanol extraction of oregano leaves, four compounds with strong an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
2
36
0
1
Order By: Relevance
“…So far, no in vivo studies have shown the protective effects of this plant on the oxidative damage induced in testicular tissue and sperm parameter's during spermatogenesis (especially due to its toxicity with finasteride, which is used to treat hair loss in men). Therefore, according to previous studies that have shown the presence of polyphenolic compounds such as apigenin, kaempferol, myricetin, quercetin, naringenin and rosmarinic acid in this plant (Chuang et al., 2018), this study can show that O. vulgare extract can improve the toxicity of reproductive production caused by finasteride in vivo. The aim of the present study was to investigate the protective effects of hydroalcoholic extract of O. vulgare L. leaves on testicular tissue using biochemical, immunohistological, apoptosis related genes, sperm parameters and antioxidant properties after finasteride damaged.…”
Section: Introductionsupporting
confidence: 56%
“…So far, no in vivo studies have shown the protective effects of this plant on the oxidative damage induced in testicular tissue and sperm parameter's during spermatogenesis (especially due to its toxicity with finasteride, which is used to treat hair loss in men). Therefore, according to previous studies that have shown the presence of polyphenolic compounds such as apigenin, kaempferol, myricetin, quercetin, naringenin and rosmarinic acid in this plant (Chuang et al., 2018), this study can show that O. vulgare extract can improve the toxicity of reproductive production caused by finasteride in vivo. The aim of the present study was to investigate the protective effects of hydroalcoholic extract of O. vulgare L. leaves on testicular tissue using biochemical, immunohistological, apoptosis related genes, sperm parameters and antioxidant properties after finasteride damaged.…”
Section: Introductionsupporting
confidence: 56%
“…25 The early action on papular erythema may be due to the fact that oregano is able to suppress the inflammation induced by propionibacterium. 26 In conclusion our in vivo study showed, in our sample with mild-moderate acne, that essential oils of myrtle and oregano have antibiotic and antiinflammatory properties, managing to improve acne lesions and retinoid erythema. Therefore, due to this double activity, they could be used, in substitution of the associated antibiotics, in the formulations with retinoids.…”
Section: Discussionmentioning
confidence: 52%
“…A large content of flavonoids luteolin-7- O -glucoside and apigenin-7- O -glucoside attained by accelerated solvent extraction with methanol is assumed to contribute to the high TPC and the FRAP value [ 18 ]. A study of Balkan et al [ 78 ] reports a connection between the TPC and DPPH scavenging activity with the presence of eriodictyol, apigenin and caffeic acid in the aqueous extract of Origanum vulgare [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol extraction of oregano leaves, yielding four compounds with strong antioxidant activity, has been reported by Chuang. Rosmarinic acid, quercetin, apigenin and carvacrol were identified by high-performance liquid chromatography [ 18 ]. Methanol has been the most widely applied solvent for the isolation of flavonoids and phenolic acids [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%